2021
DOI: 10.1002/chem.202100705
|View full text |Cite
|
Sign up to set email alerts
|

Applying Unconventional Spectroscopies to the Single‐Molecule Magnets, Co(PPh3)2X2(X=Cl, Br, I): Unveiling Magnetic Transitions and Spin‐Phonon Coupling

Abstract: Large separation of magnetic levels and slow relaxation in metal complexes are desirable properties of single-molecule magnets (SMMs). Spin-phonon coupling (interactions of magnetic levels with phonons) is ubiquitous, leading to magnetic relaxation and loss of memory in SMMs and quantum coherence in qubits. Direct observation of magnetic transitions and spin-phonon coupling in molecules is challenging. We have found that far-IR magnetic spectra (FIRMS) of Co(PPh 3 ) 2 X 2 (Co-X; X = Cl, Br, I) reveal rarely ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 113 publications
0
42
0
Order By: Relevance
“…All g → g transitions in D 4 h are technically dipole forbidden, but the use of point group D 4 shows that A 2 → A 1 is dipole allowed with z polarization and A 2 → E is dipole allowed with x , y polarization, while A 2 → A 2 , B 1 , and B 2 are all forbidden, so that the two higher energy transitions are dipole allowed by these criteria. The fit value for B is 74% of the free-ion value, thus, a plausible nephelauxetic effect, and the bonding parameters are plausible as well. , Specifically, the dmpe ligand is a stronger σ-donor and weaker π-acceptor than PPh 3 , at least in comparison with MCl 2 (PPh 3 ) 2 (M = Co II , Ni II ), which is as expected for these alkyl versus aryl (and chelating versus monodentate) phosphines . An edited listing of the Ligfield output is given in Table S3A.…”
Section: Results and Analysismentioning
confidence: 70%
See 1 more Smart Citation
“…All g → g transitions in D 4 h are technically dipole forbidden, but the use of point group D 4 shows that A 2 → A 1 is dipole allowed with z polarization and A 2 → E is dipole allowed with x , y polarization, while A 2 → A 2 , B 1 , and B 2 are all forbidden, so that the two higher energy transitions are dipole allowed by these criteria. The fit value for B is 74% of the free-ion value, thus, a plausible nephelauxetic effect, and the bonding parameters are plausible as well. , Specifically, the dmpe ligand is a stronger σ-donor and weaker π-acceptor than PPh 3 , at least in comparison with MCl 2 (PPh 3 ) 2 (M = Co II , Ni II ), which is as expected for these alkyl versus aryl (and chelating versus monodentate) phosphines . An edited listing of the Ligfield output is given in Table S3A.…”
Section: Results and Analysismentioning
confidence: 70%
“…The fit value for B is 74% of the free-ion value, 31 thus, a plausible nephelauxetic effect, 38 and the bonding parameters are plausible as well. 39,40 Specifically, the dmpe ligand is a stronger σ-donor and weaker π-acceptor than PPh 3 , at least in comparison with MCl 2 (PPh 3 ) 2 (M = Co II , 41 Ni II 42 ), which is as expected for these alkyl versus aryl (and chelating versus monodentate) phosphines. 43 An edited listing of the Ligfield 25 output is given in Table S3A.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…9–11 The anisotropic Co( ii ) complexes have been deeply studied with the results of various Co( ii )-based SIMs with different coordination geometries and environments, 12–19 among which the four-coordinate Co-SIMs are of particular interest. Most of the reported four-coordinate Co( ii )-SIMs usually contain a mixed donor set from N, P, As, O, S, Se and/or halides with the coordination moieties such as [CoN 2 N′ 2 ], 20,21 [CoNN′ 3 ], 17,22,23 [CoN 2 O 2 ], 24–26 [CoN 2 S 2 ], 27 [CoL 2 X 2 ] (L 2 = N 2 , 28,29 P 2 , 30–37 O 2 , 38 S 2 , 33,39,40 C 2 , 41 X = halide), [CoN 3 X], 42 and [CoNX 3 ]. 43 The other family includes a smaller number of homoleptic SIMs containing a CoX 4 unit (X = O, 44 S, 44,45 Se, 44 Te, 46 N, 47 Cl 48 ) with four identical donors.…”
Section: Introductionmentioning
confidence: 99%
“…The four-coordinate Co( ii )-SIMs with phosphorus ligands have been relatively less studied. Only those with the [CoP 2 X 2 ] core are known, 30–37 which are summarized in Table S2 (ESI) †. Thus, we have synthesized two Co( ii ) complexes with the [CoPX 3 ] − (X = halide) moiety, in which the Co( ii ) centre is coordinated with one triphenylphosphine and three halogen ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that intramolecular vibrations are responsible for mediating spin–phonon relaxation in most mononuclear magnets in the temperature regime of interest (∼tens of K), hereafter referred to as spin–vibronic relaxation, also known as local mode process. It should be noted that such spin–phonon coupling has recently been applied to describe Raman relaxation process as well. , Despite such knowledge, spin–vibronic relaxation nonetheless remains difficult to control experimentally. The elimination of low-frequency molecular vibrational modes has been proposed as one strategy to minimize spin–vibronic relaxation, but systematic experimental investigations validating this approach are lacking, in large part due to the challenges inherent in achieving systematic control over molecular vibrations while maintaining the electronic structure of the metal center.…”
Section: Introductionmentioning
confidence: 99%